a) x=3 and x=-6 will make the denominator terms zero, hence x may not have those values.
b) no solution
The left side can be written over a common denominator so as to make the equation be ...
((x+6) -3(x-3))/((x-3)(x+6)) = 9/((x -3)(x +6))
(-2x +15)/((x -3)(x +6)) = 9/((x -3)(x +6)) . . . . simplify
-2(x -3)/((x -3)(x +6)) = 0 . . . . . . . . . . . . . . . . subtract the right side
-2/(x+6) = 0 . . . . . . . . . . . . . . . . . . . . . . . . . . cancel factors of (x -3)
This equation has no solution. (There is no value of x that will make -2 = 0.)
_____
Comment on denominator zeros
After you've seen a few instances of the equation
x + c = 0
it doesn't take long for you to recognize that the solution is ...
x = -c
That is, when a denominator factor is (x+c), the corresponding value of x that makes this factor zero is x = -c. So, a denominator factor of x+c means the domain must exclude x = -c.
Knowing this, we can write the restrictions on a rational function "by inspection" without having to do anything except mental pattern matching.
_____
Comment on the solution method
By rewriting the rational equation to be something of the form (a/b) = 0, we have the opportunity, as here, to cancel factors that would otherwise result in extraneous solutions. Then, we don't have to be concerned with whether or not the solutions found are extraneous.